The Contribution of Nongovernment Organisations in the Enhancement of The Social Economic Welfare of the Street Children: A Case Study of Lift up Jesus Child Development Center in Kabale Municipality Kabale District. - Ntabangaryino, James (Kabale University, 2023)
Th is study investigated the contributions of nongovernment organizations in supporting street children's access social economic welfare in Lift up Jesus Kabale municipality. The study had three objectives: assess the effectiveness of the existing policies on the rights of children in assisting street children to access social economic welfare on the rights of children; examine the non-government organization's responsibilities to the problem of street children. A mixed method was used to access information through questionnaires, interviews, and documentary review from 70 respondents of whom 20 were parents, 30 were street children. The rest were education officials in different levels, one Regional Administrative Secretary, five ward executive officials, five Non-Governmental organization representatives, 6 local leaders, and religious leaders. The key findings indicated that although the government of Uganda has ratified the United Nations Convention on the Rights of the Child (UNCRC), the African Youth Charter 2006, and the Convention on the Elimination of all kinds of Discrimination against children, it has not been able to provide ways in which street children access those rights including a right to development through accessing education. Furthermore, although the community members understand their role in supporting street children, they do not feel responsible to supporting them or even advocating for the rights of street children. The study recommended that the non-government organization should devise a way to ensure that all children include street children have the right to education and to other social and economic benefits. However, several church-founded and community-based organizations have played a significant role in rehabilitating street children to turn them into productive citizens. These organizations provide children with school fees, scholastic materials, and medical care. The study recommends that the government and non-government organizations should aim at promoting poverty alleviation programs to strengthen people's economic bases, sensitizing parents to stop administering corporal punishments on children, and observing children's rights. More child centers and orphanages should be built to absorb all children on the streets